2012
DOI: 10.1002/uog.11155
|View full text |Cite
|
Sign up to set email alerts
|

Does three‐dimensional power Doppler ultrasound predict histopathological findings of uterine fibroids? A preliminary study

Abstract: Objectives To compare three-dimensional (3D) (OR, 0.6 (95% CI,, P < 0.05) and VFI (OR, 0.4 (95% CI,, P < 0.05). Conclusion Vascular density, ischemic necrosis and histological cellular activity score are statistically significantly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Certain limitations of the study need to be highlighted. We did not analyze the intraobserver variability for 3D power Doppler indices but measurement of these indices has been shown previously to have good intraobserver agreement. We did not perform any histological analyses because fibroid specimens were not available after UAE.…”
Section: Discussionmentioning
confidence: 99%
“…Certain limitations of the study need to be highlighted. We did not analyze the intraobserver variability for 3D power Doppler indices but measurement of these indices has been shown previously to have good intraobserver agreement. We did not perform any histological analyses because fibroid specimens were not available after UAE.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound features of leiomyoma with bizarre nuclei (bizarre/symplastic/atypical leiomyoma), mitotically active leiomyoma, cellular and highly cellular leiomyoma, dissecting leiomyoma and leiomyoma with increased cellularity, no atypia or mitotic figures and increased vascularity may have the same macroscopically pathological features as do fibroids and may have increased vascularity, as this feature seems to be related to cellularity. A cotyledonoid leiomyoma or cotelydonoid dissecting leiomyoma is a nodular tumor with placenta‐like echogenicity on ultrasound, but may also be cystic.…”
Section: Ultrasound Findings Associated With Pathologymentioning
confidence: 99%
“…In addition, to our knowledge no previous studies have been performed to assess reproducibility of 3D PDUS vascular parameters of fibroids. Up to now, one prospective cohort study reported a positive correlation between 3D PDUS parameters (namely, VI and VFI) and histopathological vascular parameters in fibroids . The aim of this study was to identify vascular parameters in the assessment of fibroids and to evaluate their reproducibility.…”
mentioning
confidence: 97%